Operational Reliability and Signature Analysis of an Indigenous Plantain Rotary Drying Machine - Adeyeri, Michael Kanisuru; Ayodeji, Sesan Peter; Olutomilola, Emmanuel Olatunji; Badejo, Adebanjo Ayobamidele; Olajide, Ibukunoluwa A.; Oluwatayo, Ayodeji Segun (Journal of Science, Technology and Innovation Research, 2026)
The behavioral mode of machinery is a function of its reliability. Also, machine’s reliability is defined by functionality of the various subsystems, devices and components that make up the machine. Thus, the signature of a locally developed rotary dryer has been understudied in this research to determine its behavioral pattern for its maintainability. The plantain rotary dryer comprises heater, blower, electric motor, and roller and gear drive system. The reliability function is derived from the principle of conditional probability. Also, sensors were attached to the machine components and data logger was used to retrieve temperature, sound, and vibration data at varying operations under both normal and imposed degraded conditions. The regression results from analysis of the retrieved data were compared with the system’s network modelling output, a series/parallel reliability network behavioral mode was established as the signature of the plantain rotary dryer. Also, the vibration data modelling of the rotary drying machine output shows that 0.06%, 0.04% and 0.05% of the variation in behavioral signature at: no degradation no loading; no degradation and loaded state; and degradation under loaded state operation conditions are accounted for by a linear, linear and polynomial relationship respectively. In the same vein, the temperature data modelling for the rotary dryer shows that 1.4%, 9.3% and 1.96% characteristic signature at: no degradation no loading; no degradation and loaded state; and degradation under loaded state operation conditions are accounted for by a logarithmic, polynomial and linear relationship respectively. However, these are significantly low due to the aging of the bought out components with an estimated reliability of 0.28. Nevertheless, for commercialization of the machine, newly manufactured components are recommended for development of the rotary drying machine to increase its reliability and maintainability.